2002
DOI: 10.1046/j.1529-8019.2002.01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylaxis in dermatologic patients receiving immunosuppressive therapy

Abstract: Despite substantial advances in developing more selective agents, immunosupressive therapy is still associated with serious complications. This article summarizes the preventive measures that can significantly reduce the incidence or severity of immunosupressive side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…All patients had also a concomitant antifungal treatment against oropharyngeal candidosis, this consisting of miconazole gel applied once or twice daily, or nystatin (4 mL qid) or fluconazole rinses (5 mL bid). To prevent corticosteroid‐induced osteoporosis, some patients needed also to take sodium clodronate 100 mg/3.3 mL injection monthly, 1000 mg of calcium carbonate and 400 IU of vitamin D daily until 2011; later, the usual prescription was of alendronic acid (70 mg weekly) and 400 IU of vitamin D daily.…”
Section: Methodsmentioning
confidence: 99%
“…All patients had also a concomitant antifungal treatment against oropharyngeal candidosis, this consisting of miconazole gel applied once or twice daily, or nystatin (4 mL qid) or fluconazole rinses (5 mL bid). To prevent corticosteroid‐induced osteoporosis, some patients needed also to take sodium clodronate 100 mg/3.3 mL injection monthly, 1000 mg of calcium carbonate and 400 IU of vitamin D daily until 2011; later, the usual prescription was of alendronic acid (70 mg weekly) and 400 IU of vitamin D daily.…”
Section: Methodsmentioning
confidence: 99%
“…15,45 Our study found that acquisition of PCP is rare in patients not infected with HIV and receiving systemic immunosuppressive medications for conditions with prominent dermatologic manifestations. These findings do not support the practice of routine PCP prophylaxis in unselected adult dermatology patients who require treatment with immunosuppressive medications.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies have also described probable risk factors contributing to PJP occurrence in patients with autoimmune and inflammatory diseases, revealing that corticosteroids, immunosuppressants, interstitial lung disease, high disease activity, lymphopenia, hypoalbuminemia, and advanced age (C 65 years) may all predispose patients to a higher risk of developing PJP [40,46,47]. Among these factors, corticosteroid use is well established [48,49]. However, there is no consensus on the threshold corticosteroid dose that warrants routine prophylaxis for PJP.…”
Section: Discussionmentioning
confidence: 99%